THE EFFECTIVITY OF BUILDING LOCAL CULTURAL KNOWLEDGE FOR GENERATION Z OF INDONESIA IN THE DIGITAL ERA THROUGH INSTAGRAM - Brillian Nathanael Wijaya; Kevin Kumala; Moses Glorino Rumambo Pandin (Universitas Muhammadiyah Tapanuli Selatan, 2022)
National identity will be preserved in a nation and its people only if they know their own nation. Indonesia is a multicultural nation consisting of 1.340 ethnic groups according to the census data of the Indonesian Central Statistics Agency in 2010. Each ethnic group has its own cultural characteristics, and each of these cultures makes up Indonesia. In other words, if one culture is lost, the national identity of Indonesia will also be eroded. Generation Z and subsequent generations as the nation's next-generation need to know their own nation’s ethnic group cultures so that Indonesia’s national identity is not lost amid national development. Objective: This research aims to find out how much Indonesia’s Generation Z knows about local cultures, and how effective it is to make a microblog on Instagram containing cultural information to build local cultural knowledge for Indonesia’s Generation Z in the digital era. Method: This study collected data using qualitative method through article journals and quantitative method through a survey and interview. The samples were 66 students of Universitas Airlangga as the representative of Indonesia’s Generation Z population. The researcher also created a microblog on Instagram as social media which has a close connection with Generation Z in the digital era. The microblog contains cultural information from one of Indonesia’s ethnic groups to introduce local culture in the digital era. The community's response to the microblog was analyzed to assess the effectiveness of utilizing social media in building local cultural knowledge in the digital era, especially for Generation Z. Results: The result of this study shows the lacking aspects of Indonesia’s Generation Z’s local cultural knowledge in the digital era and the usefulness of using Instagram to share local cultural knowledge. Recommendation: The researcher hopes that there will be other researchers or other parties who are willing to expand this research and efforts to build knowledge of other local cultures to Generation Z of Indonesia through other social media. Limitation: The limitation of this study is that this study only discusses the relationship between Indonesia’s Generation Z and Indonesia’s local culture in the digital era.